The Impact of a suggested training program Based on Small Sided- Games on Developing Focus Attention among Soccer Players. - رحمون, محمد أمين; بوعصيدة , أنيسة; سالمي , عقبة (sports creativity, 2025)
mall sided-games have become the secret of the success of many coaches in the field of team games due to their usefulness in developing physical, skill, tactical, and psychological qualities. In soccer, this method was used because it saves time and effort in the training process and also increases the activity and vitality of the players towards training when It has an element of surprise and competition. This method was included by the researcher in order to improve the focus of attention for the soccer players and to know the individual differences between them in this field, where the experimental method was relied on in the manner of the two equal groups (a control group and an experimental group) and the research sample included 20 players from USC Football team. The researcher conducted the pre-test using the attention methods test in group games by Dr. Muhammad Hassan Allawi, then a training program based on small sided-games (5 against 5) was applied with a total of 18 training units, and after completing the application of the program, the researcher conducted the post-test where we recorded the effect of Positive for the program applied in the development of concentration of attention among the study sample, and the researcher recommended the need to pay attention to the psychological aspect in general and focus attention in particular, as it is related to the majority of soccer skills.